FAKTOR-FAKTOR YANG BERHUBUNGAN TERHADAP DERAJAT BERAT INFEKSI VIRUS DENGUE PADA PASIEN DEWASA YANG DIRAWAT DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR BALI - Made Wulan Utami Dewi; Sianny Herawati; A.A. Ngurah Subawa (E-Jurnal Medika Udayana, 2017)
Dengue virus belongs to the genus Flavivirus that can be transmitted to humans by the bite of the Aedes aegypti mosquito. Dengue virus infection has a high mortality and morbidity rates almost throughout the world. Diagnosis has been classified by degree of clinical manifestation according to WHO 1997, confirmed through clinical signs and symptoms and laboratory tests The aim of this study was to examine the relationship between leukocyte count, lymphocyte count, hematocrit and platelet count with a severity degree of dengue virus infections, according to WHO criteria in 1997 in adult patients admitted to the General Hospital Sanglah 2015. This study was cross-sectional analytic study on 90 patients with dengue infection using secondary data. Samples are adult patients with dengue infection aged > 12 years in the medical records contained the results of the leukocyte count, lymphocyte count, hematocrit and platelet count were treated at Sanglah Hospital in Bali on the period January 1 to December 31, 2015. The results showed that there is no significant relationship between the number of leukocytes with the lowest degree of severe dengue infection (p = 0.354; r = -0.099), there is no significant relationship between low lymphocyte count with severity of dengue infection (p = 0.636, r = -0.051), there is no significant relationship between hematocrit value with the highest degree of severe dengue infection (p = 0.293; r = 0.112), and obtained negative relationship weak significant between platelet counts with the lowest degree of severe dengue infection (p = 0.009; r = -, 0275). Our results suggest that effort on early prevention and detection of dengue infection is important to reduce morbidity and mortality cause by Dengue Infection. Keywords: Leukocyte count, lymphocyte count, platelet count, hematocrit and severity of dengue infection.